2016
DOI: 10.4103/0973-1296.185771
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Massoia bark in combating immunosuppressed-related infection

Abstract: Background:As part of our search for new potential natural resources to eradicate infection, we have revealed the prominent potency of massoia bark (Massoia aromatica Becc, Lauraceae) in combating immunosuppressed-related infection.Materials and Methods:The extract was prepared by macerating the pulverized dried bark in ethanol 95%, followed by solvent evaporation. The oil was extracted from the dried bark by steam-hydrodistillation of which preparative thin-layer chromatography was performed on the oil to iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…The results of the in vitro assay supported the results of Hertiani et al [ 9 ], who reported that an increase in the phagocytic activity of macrophages is related to the increase in the content of C-10 massoialactone. The infusion method can be used to efficiently extract the active compound from the bark of the Massoia plant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the in vitro assay supported the results of Hertiani et al [ 9 ], who reported that an increase in the phagocytic activity of macrophages is related to the increase in the content of C-10 massoialactone. The infusion method can be used to efficiently extract the active compound from the bark of the Massoia plant.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is also interesting to find out whether the tannin and cinnamaldehyde also contribute in modulation of the macrophage activity following sample application. Nevertheless, C-10 massoialactone as the active compound exhibits a broad-spectrum antimicrobial activity against planktonic and biofilm cultures [ 9 ]. This activity may enhance the potential value of Massoia bark as an immunomodulator in responses to microbial infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carum copticum (bishop's weed) seeds EO compounds: α-pinene and carvacrol [34] Eucalyptus globulus (eucalyptus) [23,24] Eugenia caryophyllata [35] Massoia aromatica bark EO and massoialactone [36,37] Melaleuca viridiflora (niaouli) [38] orange EO, and its components: Limonene, linalool, and citral [39] Panax ginseng (ginseng) [40] Salvia officinalis (sage) [41] Syzygium aromaticum (clove) [41] Zanthoxylum rhoifolium [42] Zingiber officinale (ginger) [41] Dietary Supplementation for Livestock and Fish a blend of thyme (Thymus vulgaris), peppermint (Mentha piperita), and eucalyptus (Eucalyptus globulus) [43] a blend of thymol and carvacrol [44] a blend of thymol and cinnamaldehyde [45][46][47][48] Allium sativum (garlic) [49] Ducrosia anethifolia [50] Eucalyptus globulus (eucalyptus) [51] Juniperus communis (juniper) [49] Ocimum americanum (American basil) [52] Origanum onites [53] Origanum vulgare (oregano) [54] Satureja hortensis (savoury) [55] Thymus vulgaris (thyme) [56] Human Studies a blend of lavender (Lavandula angustifolia), cypress (Cupressus sempervirens), and sweet marjoram (Origanum majorana) [57] a blend of orange sweet (Citrus sinensis), true lavender, and marjoram sweet (Origanum majorana) [58] a blend of sweet orange (Citrus aurantium), lavender (Lavandula angustifolia), and sandalwood (Santalum album) [59] Chamaecyparis obtusa (hinoki cypress) [60] Citrus fragrance (lemon oil+orange oil+bergamot oil+cis-4-hexenol) [61] ginger EO [62] grapefruit, fennel, pepper, lavender, patchouli, and rose [63] La...…”
Section: In Vitro Investigationsmentioning
confidence: 99%
“…Massoia (Massoia aromatica) bark infusion containing in low doses C-10 massoialactone, the major component of massoia bark EO, was administered orally to rats every day for 14 days in a study conducted by Hertiani et al, and the effects on the phagocytic activity of peritoneal macrophages were evaluated [36]. In a previous in vitro experiment massoia bark EO and C-10 massoialactone were found to enhance the phagocytic activity of mouse macrophages, and the phagocytosis stimulation was correlated to the massoialactone content [37]. Following the treatment with massoia bark infusion, the phagocytic activity of macrophages significantly increased in rats [36].…”
Section: In Vivo Pre-clinical Studiesmentioning
confidence: 99%